Faktor-faktor yang Berhubungan dengan Perilaku Seksual Pranikah pada Remaja - Rosa Riya; Lili Ariska (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The Indonesian Health Demographic Survey (SDKI 2017) stated that 80% of women and 84% of men claimed to have dated. Among women and men who had had premarital sexual intercourse 59% of women and 74% of men reported starting sexual intercourse for the first time at the age of 15-19 years. The highest percentage occurred at the age of 17 years as much as 19%. Among adolescents who have had sexual intercourse, 12% of women have experienced an unwanted pregnancy. Adolescence is a stage between childhood and adulthood. Premarital sex behavior in adolescents is any desire-driven adolescent behavior with both the opposite sex and the same sex that was carried out before the existence of an official relationship as a husband and wife. Some of the factors that influence sexual behavior in adolescents include developmental factors, external factors, societal factors and behavioral factors of adolescents themselves. This study uses an analytical descriptive research design with a cross section method. The sample in this study was 76 people taken with the total sampling technique. This research was conducted at Madrasah Aliyah Bustanul Ulum Tanjung Jabung Timur. The data will be analyzed univariately and bivariately using chi square statistical tests. The results of this study showed that most respondents had good knowledge, had a positive attitude, had a moderate parental role, had moderate peers and had non-risky premarital sexual behavior as many as 45 respondents (59.2%). There is no knowledge relationship with premarital sexual behavior with a value of p=0.799. There is an attitudinal relationship (p=0.046), parental role (p=0.002) and peers (p=0.000) with premarital sexual behavior. The results of this study show that the factors that influence adolescent premarital sexual behavior include attitudes, the role of parents and peers. While the factor that does not affect is knowledge.